Using SEM-PLS to examine the correlation between habit of mind and belief of mathematics pre- service students - Kurniasih, Meyta Dwi; Sukestiyarno, YL; Wardono, Wardono; Asih, Tri Sri Noor (Edelweiss Applied Science and Technology, 2025)
Mathematical belief, encompassing cognitive, affective, and dispositional aspects, fundamentally shapes individuals’ attitudes toward mathematics. It reflects seriousness, confidence, and subjective stances in mathematical thinking and learning. In teacher education, prospective teachers’ beliefs significantly influence their instructional choices and student achievement. This study investigates the direct effect of Habit of Mind on mathematical belief using second-order confirmatory factor analysis within a Structural Equation Modeling (SEM) framework. Data from 200 prospective mathematics teachers were collected via a cross-sectional survey. Results indicate a strong, positive impact of Habit of Mind on mathematical belief. Importance-Performance Map Analysis (IPMA) further suggests that fostering consistent, reflective thinking habits enhances mathematical beliefs. Among Habit of Mind dimensions, Applying Past Knowledge to New Situations, Metacognition, and Thinking Interdependently emerged as the most influential. These cognitive dispositions can be systematically developed through well-designed instructional strategies in university settings. The study highlights the necessity of integrating Habit of Mind development into teacher education programs to strengthen mathematical beliefs and support more effective mathematics teaching and learning.